Paradigm Shift of Scale in Landscape Architecture—Towards a Planetary Observation - Nickayin, Samaneh Sadat (Sustainability, 2022)
In the era of globalisation, when the whole planet is urbanised and planners debate “planetary urbanization”, economists discuss “global cities”, ecologists describe the planet’s biodiversity hotspot connections, and climate change warns of a “global” crisis, it might be necessary to shift the paradigm of the landscape planning scale from local and regional scale to an adequate scale of challenges—planetary scale. The era of holistic approaches necessitates a review in local landscape planning in line with global drivers, and that is why most schools of thought have moved towards “planetary visions” to resolve the global challenges. In prospect for the planet’s future, with the bourgeoning of the next billion people, under the pressure of climate change and implosion/explosion of planetary urbanisation, shortage of land is one of the hot topics, as well as humanity’s attempt to manage the planet as a “whole” system to guarantee the economic resources and protect the biodiversity. Concerning some global landscape connectivity projects, the paper focuses on the importance of “planetary scale” to guarantee the proper understanding of relationships between landscape design, urbanization and ecological advocacy.